Inferences from a community study about non-epileptic events - Marleide da Mota Gomes; Leandro Albuquerque Lemgruber Kropf; Erica da Silva van Beeck; Ivan Luiz de Vasconcellos Figueira (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To demonstrate the epidemiological importance of the different types of non-epileptic events (NEE) in a low-income urban community. METHOD: The patients suspected of having epilepsy, who were detected in the first phase (screening one) of this prevalence study, were interviewed by a neurologist in a non-structured neurological interview. These NEE were classified as physiological and psychogenic, subdivided by various types. The psychogenic NEE were classified according to the DSM-IV criteria. RESULTS: We compared the cases suspected of having epilepsy (n=176) with those not suspected (n=806) and discovered that those cases suspected of having epilepsy had a greater median age (<0.01) and female predominance (p<0.01). Among the cases suspected of having epilepsy there were different diagnosis: epileptic events without identifiable cause (n=20) or with identifiable causes (e.g., febrile convulsions and eclampsia). The most prevalent diagnosis for those suspected of having epilepsy was syncope (n=63; 35.8%). In terms of physiological events, the most frequent were: epileptic seizures, paroxysmal toxic phenomena (including alcoholism) and brain trauma, besides syncope; in terms of psychogenic events the most frequent were: dissociative and anxiety disorders. Regarding gender differences, paroxysmal toxic problems were significantly more prevalent in men (p= 0.02), and dissociative disorders (p=0.01) in women. CONCLUSION: This survey confirms the epidemiological importance of syncope in a populational sample with NEE. However, among the psychogenic disorders of this NEE sample, the most frequent were dissociative and anxiety phenomena. This finding contrasts with the literature based on samples from tertiary epileptic centers with video-EEG resources, which found somatoform disorders to be more prevalent than dissociative and anxiety phenomena.